1987
DOI: 10.1007/bf02009044
|View full text |Cite
|
Sign up to set email alerts
|

Non cytotoxic guinea-pig mesenteric mast cell stimulation by protamine

Abstract: Protamine stimulates guinea-mesenteric mast cells in a concentration-dependent manner, both histamine release and mast cell degranulation being correlated. Mast cell stimulation is blocked by 2,4-DNP (0.03 mM), low (0 degrees C) and high (45 degrees C) temperature. The inhibitory effect by 2,4-DNP is reversed by glucose (5.0 mM), while incubation at 37 degrees reverses that by low and high temperature. Lack of calcium from the incubation medium does not influence mast cell stimulation by protamine. However cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is well established that IgE and IgG to protamine constitute major risk factors for developing adverse reactions to protamine [1]. However, the identification of several apparently immunoglobulin-independent effects of protamine [4][5][6]8] indicates that the mechanism of action may be complex. Since protamine is an established heparin antagonist in vivo it is plausible that the compound will interact with endogenous chymase/heparin PG complexes, thereby decreasing the heparin-dependent activities displayed by the proteases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that IgE and IgG to protamine constitute major risk factors for developing adverse reactions to protamine [1]. However, the identification of several apparently immunoglobulin-independent effects of protamine [4][5][6]8] indicates that the mechanism of action may be complex. Since protamine is an established heparin antagonist in vivo it is plausible that the compound will interact with endogenous chymase/heparin PG complexes, thereby decreasing the heparin-dependent activities displayed by the proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that elevated serum levels of IgE or IgG to protamine increase the risk of obtaining adverse reactions to the protein [2,3]. Other reports have shown that protamine can interact directly with mast cells (MC), causing non-immunological histamine release [4,5]. In addition, inhibition of plasma carboxypeptidase N [6] and activation of the complement system [7,8] by protamine have been reported.…”
Section: Introductionmentioning
confidence: 99%